2021
DOI: 10.1177/0040059921994599
|View full text |Cite
|
Sign up to set email alerts
|

Manipulative-Based Instructional Sequences in Mathematics for Students With Disabilities

Abstract: Manipulative-based instructional sequences—including both concrete and virtual manipulative instructional sequences—are evidence-based or research-based mathematical interventions for students with disabilities. However, as options for manipulative-based instructional sequences increase, educators need support in deciding the best approach. In this manuscript, we provide practical tips for educators to make decisions about selecting and implementing manipulative-based instructional sequences for students with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Mathematics instruction using virtual manipulatives can be implemented in three ways: (a) teacher-led instruction, (b) teacher-guided instruction, and (c) technology-assisted instruction (Bouck et al, 2021; Park, Bryant, & Shin, 2021; Shin et al, 2021). These instructional methods are effective for teaching mathematics to a wide range of grade levels.…”
Section: Use Of Virtual Manipulativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematics instruction using virtual manipulatives can be implemented in three ways: (a) teacher-led instruction, (b) teacher-guided instruction, and (c) technology-assisted instruction (Bouck et al, 2021; Park, Bryant, & Shin, 2021; Shin et al, 2021). These instructional methods are effective for teaching mathematics to a wide range of grade levels.…”
Section: Use Of Virtual Manipulativesmentioning
confidence: 99%
“…Virtual manipulatives can be included in various technology environments, such as single representation (i.e., interactive image only), multiple representation (i.e., interactive visual models accompanied with numerical or text information), tutorials, gaming , and simulation (Moyer-Packenham & Bolyard, 2016), encouraging students to engage in learning. Studies have revealed that students with disabilities who received mathematics interventions using virtual manipulatives showed both immediate effects and growth over time in various concepts and subjects within mathematics (Bouck et al, 2021; Park, Bryant, & Shin, 2021; Shin et al, 2021).…”
mentioning
confidence: 99%
“…(Bouck et al, 2018a;Soares et al, 2018). To support mathematics learning of the students with learning disabilities, studies involving mathematics instruction with concrete and virtual manipulatives have been conducted by several researchers (i.e., Bouck et al, 2017Bouck et al, , 2021Satsangi & Bouck, 2015;Satsangi et al, 2016) in the past. To synthesise the findings of the effectiveness of mathematics instruction involving manipulatives, Bouck and Park (2018) have reviewed 36 past studies.…”
Section: Research Domain 2: Mathematics Learning Of Students With Lea...mentioning
confidence: 99%
“…Virtual manipulatives can be included in various technology environments, such as single-representation (interactive image only), multiple-representation (interactive visual models accompanied with numerical or text information), tutorials, gaming, and simulation (Moyer-Packenham & Bolyard, 2016), encouraging students to engage in learning. Studies have revealed that students with disabilities who received mathematics interventions using virtual manipulatives showed both immediate effects and growth over time in various concepts and subjects within mathematics (Bouck et al, 2021;Park, Bryant, et al, 2021;Shin et al, 2021).…”
Section: Mathematics Instruction For Students With Disabilities: Applied Examples Using Virtual Manipulativesmentioning
confidence: 99%
“…Mathematics instruction using virtual manipulatives can be implemented in three ways: a) teacher-led instruction, b) teacher-guided instruction, and c) technology-assisted instruction (Bouck et al, 2021;Park, Bryant, et al, 2021;Shin et al, 2021). These instructional methods are effective for teaching mathematics to a wide-range of grade levels.…”
Section: Use Of Virtual Manipulativesmentioning
confidence: 99%